2020
DOI: 10.1055/s-0040-1702986
|View full text |Cite
|
Sign up to set email alerts
|

Marked Directional Skull Asymmetry in the Araucan Horse

Abstract: Background Deviations from the perfect symmetry of normally bilateral symmetrical characters occur during individual development due to the influence of multiple factors. Fluctuating asymmetry (FA) is the random developmental variation of a trait (or character) that is perfectly symmetrical, on average, across a population. Directional asymmetry (DA) occurs when one side of the pair of body sides is strongly more marked. Objective We investigated the presence and level of skull FA and DA in the Arauc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This was attributed to the effects of mechanical forces. The dominance of one side may determine differential mastication and bone remodeling, contributing to directional asymmetry [80].…”
Section: Fluctuating Asymmetry Using Geometric Morphometrics In Agroecosystemsmentioning
confidence: 99%
“…This was attributed to the effects of mechanical forces. The dominance of one side may determine differential mastication and bone remodeling, contributing to directional asymmetry [80].…”
Section: Fluctuating Asymmetry Using Geometric Morphometrics In Agroecosystemsmentioning
confidence: 99%
“…Initial population bottlenecks associated with the domestication process, causing inbreeding and an accumulation of deleterious mutations (i.e., genetic stress) (e.g., Marsden et al, 2016), may also result in increased FA among domesticated animals. Domesticates have been the subject of several studies using FA, including for the cranium of pigs (Parés Casanova & Esteve‐Puig, 2014), horses (Parés Casanova et al, 2020), sheep (Parés Casanova & Bravi, 2014; Parés Casanova, 2019), and dogs (Drake & Klingenberg, 2010), as well as the metacarpals of sheep (Parés‐Casanova, 2014), the horns of mountain goats (Côté & Festa‐Bianchet, 2001) and hooves and forelimbs of horses (Wilson et al, 2009). With the exception of Drake and Klingenberg (2010), who compared wild and domestic forms, these studies were focused on small comparisons within domestic populations and revealed that FA accounts for a moderate amount of shape variance, consistent with the results across species examined here (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…The direct comparison of FA in domestic forms with that in their wild relatives has received comparatively less attention than analyses of disparity in form among domesticated species (but see Drake & Klingenberg, 2010; Pulcini et al, 2015). Nevertheless, several studies have focused exclusively on within‐population assessments of FA for small populations of individual domestic species and these indicate that a moderate magnitude of asymmetry in the cranium is common (Parés Casanova, 2019; Parés Casanova & Bravi, 2014; Parés Casanova & Esteve‐Puig, 2014; Parés Casanova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Araucanian horse constitutes an equine population typical of the ecosystem of the Araucanian plains in NE Colombia. Of great rusticity, it has hardly been studied in its ecological environment until recently, when investigations have been initiated aimed at its morphological description, functional study, and genetic management [13][14][15]. The Araucanian horse represents a cultural and genetic heritage adapted to the environment of the flooded savanna; therefore, a morphological study might reveal its evolutionary traits of adaptation to the environment.…”
Section: Introductionmentioning
confidence: 99%